Memaksimalkan Potensi Pustakawan: Urgensi Keterampilan ?Komunikasi Interpersonal dalam Lingkungan Kerja: Urgensi keterampilan komunikasi interpersonal dalam lingkungan kerja - Sumarni Inda; Azizah Nur Rafidah; Eny Supriati‎; Ayu Wulansari; Asnah Yuliana (IJAL (Indonesian Journal of Academic Librarianship), 2023)
In the digital era, the role of school librarians has evolved, making practical communication skills a key component in providing quality services and supporting the learning process. This research examines the urgency of interpersonal communication skills in maximizing the potential of librarians in the library work environment at SMAN 1 Ponorogo. This study uses a qualitative method with a case study approach. Data was collected through participant observation, in-depth interviews with 3 school librarians, 5 teachers, and 10 students, and analysis of related documents. The research results show that librarians' interpersonal communication skills play an essential role in Increasing students' reading interest and visits to the library, Facilitating effective collaboration with teachers in supporting the curriculum, Increasing service efficiency and resource management, and Creating a conducive learning environment in the library. The main findings reveal that librarians with good interpersonal communication skills can better understand the information needs of students and teachers, overcome obstacles in using information technology in libraries, and play an active role in school literacy programs. This research concludes that developing the interpersonal communication skills of librarians at SMAN 1 Ponorogo needs to be a priority to optimize library functions in supporting the school's vision and mission. Recommendations include regular communication training, mentoring programs, and performance evaluations that include aspects of interpersonal communication.